2008
DOI: 10.1186/1471-2180-8-143
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis: A differential trait of the fecal microbiota of breast-fed infants

Abstract: Background: Breast milk is an important source of staphylococci and other bacterial groups to the infant gut. The objective of this work was to analyse the bacterial diversity in feces of breastfed infants and to compare it with that of formula-fed ones. A total of 23 women and their respective infants (16 breast-fed and 7 formula-fed) participated in the study. The 16 women and their infants provided a sample of breast milk and feces, respectively, at days 7, 14, and 35. The samples were plated onto different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 40 publications
(57 reference statements)
12
131
1
7
Order By: Relevance
“…Indeed, S. aureus and S. epidermidis are both common mastitis pathogens, yet in several studies examining the bacterial communities of milk produced by women free from mastitis, the presence of both of these species has been reported (18,22,28). It is therefore of great interest to understand why these species are seemingly harmless commensal organisms at some times and pathogens at others.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, S. aureus and S. epidermidis are both common mastitis pathogens, yet in several studies examining the bacterial communities of milk produced by women free from mastitis, the presence of both of these species has been reported (18,22,28). It is therefore of great interest to understand why these species are seemingly harmless commensal organisms at some times and pathogens at others.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the consensus view of maternal inheritance of the microbiome at birth, the source of the early colonizers has never been exhaustively studied. Targeted cultivation-based investigations have shown that mother-infant pairs often share strains of bifidobacteria and lactobacilli (Tannock et al 1990;Matsumiya et al 2002;Jiménez et al 2008;Albesharat et al 2011;Makino et al 2013;Jost et al 2014). Large scale 16S rRNA and metagenomic surveys have found that vaginally born infants often harbor species that can also be detected in the mother (Dominguez-Bello et al 2010;Bäckhed et al 2015), thus hinting at broad vertical transmission of the microbiota, but the same species can also be shared by unrelated individuals.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…However, there is growing evidence that the in utero environment may not be sterile, as originally thought: bacteria such as Enterococcus faecalis, Staphylococcus epidermidis, and Escherichia coli have been isolated from the meconium of healthy neonates. 13 The infant gut microbiota is more variable in its composition and less stable over time. In the first year of life, the infant intestinal tract progresses from sterility to extremely dense colonization, ending with a mixture of microbes that is relatively stable and largely similar to that found in the adult intestine.…”
Section: The Host-microbiota Dialoguementioning
confidence: 99%